Oscillatory Behavior of Second-Order Nonlinear Neutral Differential Equations - Tongxing Li; Yuriy V. Rogovchenko (Abstract and Applied Analysis)
We study oscillatory behavior of solutions to a class of second-order nonlinear neutral differential equations under the assumptions that allow applications to differential equations with delayed and advanced arguments. New theorems do not need several restrictive assumptions required in related results reported in the literature. Several examples are provided to show that the results obtained are sharp even for second-order ordinary differential equations and improve related contributions to the subject.